2015
DOI: 10.1161/jaha.115.002092
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heart Failure and Atrial Fibrillation: Insights From the Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure (ASCEND‐HF) Trial

Abstract: BackgroundPatients with acute heart failure (AHF) frequently have atrial fibrillation (AF), but how this affects patient-reported outcomes has not been well characterized.Methods and ResultsWe examined dyspnea improvement and clinical outcomes in 7007 patients in the Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure (ASCEND-HF) trial. At baseline, 2677 (38.2%) patients had current or a history of AF and 4330 (61.8%) did not. Patients with a history of AF were older than those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…This study also used exercise capacity as a variable in their analysis, which is not reported in the majority of studies. In the AHF population, the literature is consistent with the present study, demonstrating that atrial fibrillation increases overall risk of mortality and rehospitalization, but is not an independent predictor . In light of these findings, we would suggest that atrial fibrillation is not an independent predictor of mortality.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study also used exercise capacity as a variable in their analysis, which is not reported in the majority of studies. In the AHF population, the literature is consistent with the present study, demonstrating that atrial fibrillation increases overall risk of mortality and rehospitalization, but is not an independent predictor . In light of these findings, we would suggest that atrial fibrillation is not an independent predictor of mortality.…”
Section: Discussionsupporting
confidence: 89%
“…In the AHF population, the literature is consistent with the present study, demonstrating that atrial fibrillation increases overall risk of mortality and rehospitalization, but is not an independent predictor. 11,12,42 In light of these findings, we would suggest that atrial fibrillation is not an independent predictor of mortality. Patients with atrial fibrillation tend also to have several other confounding variables, including exercise capacity that is frequently not reported, which makes it increasingly difficult to identify unique predictors of mortality.…”
Section: Discussionmentioning
confidence: 89%
“…According to the results of the Worcester Heart Failure study, AF prevalence in patients with HF in 1995 was 34.5%, which increased to 41.6% in 2004 (15). In our study, the prevalence of AF was 39% in patients with ADHF, which is similar to the rates reported in the ASCEND-HF (38.2%), EHFS II (38.7%), ATTEND (39.6%), and Worcester Heart Failure (39.7%) studies but higher than the rates reported in the ADHERE and OPTIMIZE-HF studies (15,16,24,29,31,33). Meanwhile, the studies conducted in the Middle East region and Africa have reported AF prevalence rates between 14% and 18.3%, which is different from that reported in the studies conducted in the Western countries (34,35).…”
Section: Discussionsupporting
confidence: 83%
“…According to different studies, the short-and long-term prognostic importance of AF in patients with acute decompensated heart failure (ADHF) has been conflicting (4,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Several important studies have reported that the presence of AF in ADHF patients is associated with an increased risk of mortality (15,17,19).…”
mentioning
confidence: 99%
“…Among the many diseases that contribute to the development of heart failure (HF), coronary artery disease (CAD) [1], hypertension (HT) [2], obesity [3], and tachyarrhythmias, especially atrial fibrillation (AF) [4,5], play a leading role. A link between obesity-related insulin resistance (IR) and HF has also been described [6], including: alteration in glucose and free fatty acid metabolism in cardiac myocytes, induction of inflammation and oxidative stress, and promotion of overactivity of the renin-angiotensin II system [7].…”
Section: Introductionmentioning
confidence: 99%